1979
DOI: 10.1161/01.res.45.3.404
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vasodilator activity of prostacyclin (PGI2) in the cat.

Abstract: IN the lung, arachidonic acid is transformed into the cyclic endoperoxide intermediates, PGG2 and PGH 2 , by a microsomal cyclooxygenase (Nugteren and Hazelhof, 1973;Hamberg and Samuelsson, 1974). The endoperoxide intermediates then are converted by specific terminal enzymes into prostaglandins (PG), thromboxane A2, and a newly discovered bicyclic prostaglandin, prostacyclin, or PGI 2 (Nugteren and Hazelhof, 1973;Hamberg and Samuelsson, 1974;Gryglewski et al., 1976). PGI 2 is the major metabolic product formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 18 publications
2
29
0
1
Order By: Relevance
“…It has been reported that diverse agents such as hydralazine, isoproterenol, diazoxide, tolazoline, and phentolamine may be useful in the treatment of pulmonary hypertension (27)(28)(29)(30)(31). It has also been shown that prostacyclin and several prostacyclin-like substances have good vasodilator activity in the pulmonary vascular bed (15,(32)(33)(34) and it has recently been reported that prostacyclin produced a marked reduction in pulmonary arterial pressure in a patient with severe idiopathic pulmonary hypertension (35). The use of nitroglycerin in the treatnent of angina, and nitroprusside in the treatment of hypertensive emergencies and congestive heart failure, is well established (1-4).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that diverse agents such as hydralazine, isoproterenol, diazoxide, tolazoline, and phentolamine may be useful in the treatment of pulmonary hypertension (27)(28)(29)(30)(31). It has also been shown that prostacyclin and several prostacyclin-like substances have good vasodilator activity in the pulmonary vascular bed (15,(32)(33)(34) and it has recently been reported that prostacyclin produced a marked reduction in pulmonary arterial pressure in a patient with severe idiopathic pulmonary hypertension (35). The use of nitroglycerin in the treatnent of angina, and nitroprusside in the treatment of hypertensive emergencies and congestive heart failure, is well established (1-4).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the pressor effects of PGF2a, PGD2, and PGE2 or the PGH2 analog which may mimic the effects of TXA2 on the pulmonary vascular bed, the newly discovered bicyclic prostaglandin, PGI2, had vasodilator activity in the pulmonary vascular bed (23,24). The pulmonary vasodilator effects of PGI2 were modest under resting conditions but were greatly enhanced when pulmonary vascular resistance was increased actively by infusion of a vasoconstrictor substance (23). Although PGI2 had vasodilator activity, arachidonic acid when administered as a bolus, consistently increased pulmonary vascular resistance in the intact dog and cat and in the isolated dog lung (10,12,13,21,22).…”
Section: Discussionmentioning
confidence: 98%
“…The endoperoxide analog, PGF2a,f, and PGD2 all increased lung resistance and decreased dynamic compliance and in this regard were similar to but much more potent than arachidonic acid (17,21,26 (12). In contrast to the pressor effects of PGF2a, PGD2, and PGE2 or the PGH2 analog which may mimic the effects of TXA2 on the pulmonary vascular bed, the newly discovered bicyclic prostaglandin, PGI2, had vasodilator activity in the pulmonary vascular bed (23,24). The pulmonary vasodilator effects of PGI2 were modest under resting conditions but were greatly enhanced when pulmonary vascular resistance was increased actively by infusion of a vasoconstrictor substance (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations